Perfil de Fermentação e composição química da silagem de capim elefante BRS Capiaçu com aditivos em diferentes tempos de abertura - JENIFFER DA CRUZ SIQUEIRA (2024)
SIQUEIRA, J.C. FERMENTATION PROFILE AND CHEMICAL COMPOSITION OF BRS CAPIAÇU ELEPHANT GRASS SILAGE WITH ADDITIVES AT DIFFERENT OPENING TIMES. Dissertation (Master in Animal Science) - Faculty of Veterinary Medicine and Animal Science, Federal University of Mato Grosso do Sul, Campo Grande, MS, 2024. The objective was to evaluate the fermentative profile and nutritional value of Capim Elefante BRS Capiaçu silage using different additives. The experimental design was completely randomized, in a 3 x 5 factorial scheme, with three replications. The treatments evaluated were: T1 - Elephant grass (CE); T2 - CE + 10% cornmeal; T3 - CE + inoculant, opening five times after ensiling, on days 1, 7, 14, 28 and 56. Experimental PVC silos with a capacity of 3.0 kg were used, adopting a density of 500 kg of mass green per m-3. After opening the silos, the contents of dry matter (DM), organic matter (MO), crude protein (CP), ether extract (EE), neutral detergent fiber (NDF), acid detergent fiber (ADF) were quantitatively determined. , non-fibrous carbohydrates (CNF), buffer capacity (CT), pH and ammonia nitrogen (N-NH3). The data were subjected to analysis of variance and regression. The choice of models was based on the significance of the linear and quadratic coefficients, at a 5% probability level using the Tukey test. It was observed that the average DM percentages of silages were higher for treatments that used cornmeal. There was an effect of fermentation days (P